Recessive variants in COL25A1 gene as novel cause of arthrogryposis multiplex congenita with ocular congenital cranial dysinnervation disorder. Issue 4 (3rd February 2022) - Natera‐de Benito, Daniel; Jurgens, Julie A.; Yeung, Alison; Zaharieva, Irina T.; Manzur, Adnan; DiTroia, Stephanie P.; Di Gioia, Silvio Alessandro; Pais, Lynn; Pini, Veronica; Barry, Brenda J.; Chan, Wai‐Man; Elder, James E.; et al.
Abstract: A proper interaction between muscle‐derived collagen XXV and its motor neuron‐derived receptors protein tyrosine phosphatases σ and δ (PTP σ / δ ) is indispensable for intramuscular motor innervation. Despite this, thus far, pathogenic recessive variants in the COL25A1 gene had only been detected in a few patients with isolated ocular congenital cranial dysinnervation disorders. Here we describe five patients from three unrelated families with recessive missense and splice site COL25A1 variants presenting with a recognizable phenotype characterized by arthrogryposis multiplex congenita with or without an ocular congenital cranial dysinnervation disorder phenotype. The clinical features of the older patients remained stable over time, without central nervous system involvement. This study extends the phenotypic and genotypic spectrum of COL25A1 related conditions, and further adds to our knowledge of the complex process of intramuscular motor innervation. Our observations indicate a role for collagen XXV in regulating the appropriate innervation not only of extraocular muscles, but also of bulbar, axial, and limb muscles in the human.